Взаємообумовленість розвитку регіонального середовища і малого підприємництва - Толмачова, Г.Ф.; Квілінський, О.С. (Стратегія і механізми регулювання промислового розвитку, 2013)
Виявлено регіони-лідери та регіони-аутсайдери щодо мікро- і макроекономічних показників конкурентоспроможності. За допомогою побудови кореляційнорегресійних моделей визначено залежність показників малих підприємств від показників регіональної економіки, а також зворотний вплив діяльності малих підприємств на економіку регіону. Выявлены регионы-лидеры и регионы-аутсайдеры по микро- и макроэкономическим показателям конкурентоспособности. С помощью построения корреляционнорегрессионных моделей определена зависимость показателей малых предприятий от показателей региональной экономики, а также обратное влияние деятельности малых предприятий на экономику региона. The paper studies the role and place of small business in the system of the regional development. Specific features of regional organization of small business entities are specified: relative independence of economic behavior of small business entities; resolution of economic conflicts which are generated because of negative economic phenomena (reprofiling, technical reconstruction, liquidation or shadowing), creation and development of the systems of the state support of small business entities at the level of region. Ratings of Ukraine’s regions competitiveness in 2012 and 2013 are analysed. The regions-leaders and regions-outsiders are identified in relation to the micro- and macroeconomic indexes of competitiveness. To confirm a high-degree interdependence of regional features and processes of development of small business, a comparative analysis of small business development was conducted in the areas of Ukraine. On the basis of statistical information, ratings of Ukraine’s regions are built. Using quantitative indexes the method of ranging was apllied to estimate the development of small business in the regions of Ukraine. To confirm a high-degree interdependence of regional features and processes of development of small business, the research was conducted with the use of methods of mathematical statistics (cross-correlation regressive models). The connection and dependence of indexes of small business on the indexes of regional economy were established, as well as a reverse influence of activity of small enterprises on the economy of region using statistical information after 2006-2011 The research reveals a set of factors influencing the indexes which characterize a regional economy. The study found that the indexes of small business development have the connection with such regional indexes as a volume of realized services to the population and incomes of the population. Given regional indexes characterize the efficiency of the market of commodities and services, and solvency of population, and their increase stimulates the creation of new workplaces in smallbusiness and growth of volume of products realized by small enterprises. Performance of small enterprises has a considerable connection with such indexes of regional economy as a volume of foreign investments, quantity of the concerned population, volume of retail commodity turnover of enterprises in a region, volume of investments in the fixed assets and average monthly nominal earnings. These indexes of the regional economy testify to the level of the economic complex development, market infrastructure, macroeconomic environment, market of commodities, labour-market, etc. The above-mentioned statistical analysis shows that in the developed regions with a high-level industrial potential and high solvency of population small enterprises are most effective. To study a reverse influence of activity of small enterprises on a regional economy, the row of models was built, where the indexes of regional economy came forward as effective indexes in turn, and indexes which characterize the development of small enterprises served as factor signs. To expose the qualitative influence of each factor signs on effective indexes, the linear models of regression were built. The results of construction of models showed that the indexes of small enterprises have the most influence on such indexes of regional economy, as incomes of the population, volume of foreign investments, average monthly nominal earnings, volume of retail commodity turnover of enterprises in a region, volume of the realized services to the population, quantity of the concerned population of region. It is well-proved in the article, that the development of small business depends on many factors, including regional features, economic potential, use of available resources, improvement of economic structure, perfection of regulator policy in relation to small business entities in a region and others like that. These and other factors must be taken into account when developing and introducing the strategies for small business entities, and also the realization of territorial policy to support small enterprise. The results of the research show that the sector of small business so far does not have a substantial influence on the regional economy and is notdeveloped enough to provide a dynamic growth of the potential. At the same time, the dynamics of growth of indexes of small business entities in regions testifies to its internal sufficient potential, desire and possibilities of wider population to provide own forces for supporting the economic independence.